THE EFFECT OF BRAND AMBASSADORS, DISCOUNTS, AND ADVERTISEMENTS ON PURCHASING DECISIONS ON THE TOKOPEDIA MARKETPLACE - Amanda Putri; Mohamad Trio Febriyantoro; Zulkifli; Dede Suleman; Fendi Saputra; Yohanes Totok Suyoto (Asosiasi Dosen Muda Indonesia, 2022)
This study aims to analyze the effect of promotional activities such as Brand Ambassadors, Discounts, and Advertisements on Purchase Decisions on the Tokopedia Marketplace, This research was of a quantitative type with a simple random sampling technique and the data used in this study was primary data obtained from distributing online questionnaires using a google form from 114 Tokopedia consumers in Indonesia using multiple linear analysis methods and using SPSS 23 as a tool measuring. The results of this study indicate that the brand ambassador variable has no significant effect on purchasing decisions while the Discounts and Advertisements Variables have a positive and significant effect on purchasing decisions. Simultaneously, brand ambassadors, discounts, and advertisements influence purchasing decisions with a percentage of 58.1%, while the remaining 41.9% are influenced by other variables not included in this study.